2020
DOI: 10.1093/tbm/ibaa099
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of context-aware digital behavior change interventions to improve health

Abstract: Health risk behaviors are leading contributors to morbidity, premature mortality associated with chronic diseases, and escalating health costs. However, traditional interventions to change health behaviors often have modest effects, and limited applicability and scale. To better support health improvement goals across the care continuum, new approaches incorporating various smart technologies are being utilized to create more individualized digital behavior change interventions (DBCIs). The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…As some authors suggest, the inclusion of BCTs contributes to improving the potential to promote behavior change [ 31 ]. This probably justifies the employment of different BCTs in digital behavior change interventions [ 32 ]. In this sense, Webb et al [ 33 ] conclude that the inclusion of BCTs is linked to the efficacy of interventions in which digital resources are used, a possible motivator for the potential incorporation of more specific BCTs by app developers.…”
Section: Discussionmentioning
confidence: 99%
“…As some authors suggest, the inclusion of BCTs contributes to improving the potential to promote behavior change [ 31 ]. This probably justifies the employment of different BCTs in digital behavior change interventions [ 32 ]. In this sense, Webb et al [ 33 ] conclude that the inclusion of BCTs is linked to the efficacy of interventions in which digital resources are used, a possible motivator for the potential incorporation of more specific BCTs by app developers.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a recent review on mobile apps for individuals with chronic diseases [ 14 ], this study identified that participants were engaged and empowered when using the app. An increase in the activation levels may encourage health-related behaviors, such as increasing physical activity, dietary behaviors, and medication adherence [ 39 , 40 ], as well as support closer monitoring of their disease symptoms [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in eHealth technology have cultivated transactional opportunities for patients to access, share, and monitor health information [ 15 ]. Digital behavior change interventions use digital health technologies for behavior modification for the maintenance and improvement of health [ 16 ], and patients and health professionals tend to search the Internet for information about many health-related topics. In fact, 81% of all Internet users go online and search for information related to health [ 13 ].…”
Section: Introductionmentioning
confidence: 99%